Just when you think you know someone: the evolving epidemiologies of measles and pertussis. Issue 1 (February 2016) - Zahn, Matt
Abstract : Purpose of review: The epidemiologic patterns of measles and pertussis continue to evolve in the United States. Recent studies have provided important insights which impact the public health response to these diseases. Recent findings: An increase in imported cases has led to increased reports of measles disease in the United States. The burden of pertussis disease is shifting to schoolchildren who have received only acellular vaccinations as part of their childhood series. Summary: Routine childhood vaccinations protect against these diseases, but have limitations which should be recognized. Medical providers and public health practitioners will need to work together to ensure that patients are educated about the importance of vaccines, and that these vaccines are available to those who need them.